Combined use of cinnamon essential oil and MAP/vacuum packaging to increase the microbial and sensorial shelf life of lean pork and salmon. (June 2017) - Van Haute, Sam; Raes, Katleen; Devlieghere, Frank; Sampers, Imca
Highlights: Pork and salmon were dipped in 1% cinnamon oil and packaged in MAP or vacuum. Cinnamon increased microbial shelf life of pork (MAP and vacuum), but not of salmon. MAP packaged salmon had longer microbial shelf life than vacuum packaged salmon. Cinnamon was neutral towards color/odor of the foodstuffs. Marinade (10% NaCl, 2% lactic acid, pH 4) caused discoloration of pork in MAP. Abstract: The combination of cinnamon essential oil ( cinnamomum zeylanicum ) and packaging methods was assessed in order to increase the shelf life of lean pork and salmon. The foodstuffs were dipped in 1 w/w% cinnamon, and the treated foodstuffs were stored (4 °C) in vacuum or MAP package (pork in 70% O2 /30% CO2 and salmon in 60% CO2 /40% N2 ). For both packaging methods the use of cinnamon increased the microbial shelf life of pork but not of salmon. For salmon, vacuum packaged salmon reached end of microbial shelf life faster than MAP packaged salmon. Off-odors occurred faster in MAP packaged pork than in vacuum and off-odors in salmon developed independent of packaging method. Cinnamon essential oil application was neutral towards the color and odor of the food matrices. Cinnamon essential oil shows promise as antimicrobial treatment on vacuum or MAP packaged lean pork, but not on salmon.